Design of low drop-out linear voltage regulator - Zhao, Xin. (2009)
The study of power management systems has increased obviously in the past few years corresponding to the drastic increase in the use of battery powered portable devices. These power management systems usually contain several low dropout voltage regulators (LDO) with large load capacitors for the stability requirement. However, the large load capacitors cannot be integrated in these LDO devices in current CMOS technologies, so extra space will be occupied by these external load capacitors.